Technical and Economic Evaluation and Optimization of an Off-Grid Wind/Hydropower Hybrid System - Reza Alayi; Yaser Ebazadeh; Hossein Monfared; Salamollah Mohammadi-Aykar; Laveet Kumar; Alfian Ma’arif; Eskandar Jamali (International Journal of Robotics and Control Systems, 2023)
Owing to global population growth, more fossil fuels are being used to meet the energy demand, which has led to increases in environmental pollution. Therefore, alternative sources such as renewable energy can be employed to meet some of the needs. Renewable energy has been criticized for its related problems such as downtime and high investment costs. In this study, a system was proposed to address these two problems by integrating wind and hydropower turbines, in Khalkhal, Ardabil, Iran as a case study. To appraise the system, an economic model was generalized, and an Ant Colony Optimization (ACO) method aiming to reduce investment costs was, implemented. The results show that to cover 100% of the required energy demand with a hybrid system of wind and hydropower turbines, the total cost of this system will be $ 202138. Also, the Cost of Energy (COE) per unit of generated power with the hydropower system, wind, and battery storage is gauged at 0.261 $/kWh. For the case study, to supply the required energy demand, 10 wind turbines and 23 kVA batteries, as well as a 14.6 kW hydropower turbine are required.